Strategi Pembangunan Nasional Terhadap Ketimpangan Ekonomi Antar Daerah Perspektif Ekonomi Islam - Taufik Arnanda Marpaung; Muhammad Imam Daei; Dorlan Habibi; Nurhayati Harahap (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Indonesia has a significant problem of economic inequality between regions. This can give rise to inequality and social injustice. The government, in its efforts to achieve economic equality between regions in its national development strategy, has provided several policies, however, it also needs a national development strategy with an Islamic perspective to perfect these policies. This study employed a qualitative approach as its research methodology, specifically focusing on library research. A qualitative approach allows researchers to understand complex and multidimensional phenomena. In facing the challenges, challenges and failures in the national development strategy in Indonesia in the last 10 years, Islamic Economics can provide alternative solutions that can strengthen the parts that according to Islamic Economics must also be considered in order to strengthen the National Development strategy that can minimize and neutralize, one of which is by paying attention to Sharia Economic Principles in terms of development such as justice, balance and poverty. Therefore, the national development strategy implemented must pay attention to these principles. From the standpoint of Islamic economic development, Indonesia's development focus for the past ten years has been irrelevant. This is a result of the Indonesian government continuing to focused on infrastructure development and is not fully in accordance with sharia principles, and is lacking in improving the aspect of human resources.